2019
DOI: 10.3233/nre-192687
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of somatosensory interventions on somatosensory, motor and functional outcomes in the upper limb post-stroke: A systematic review and meta-analysis

Abstract: BACKGROUND: Research mainly focuses on motor recovery of the upper limb after stroke. Less attention has been paid to somatosensory recovery. OBJECTIVE: To review and summarize the effect of upper limb somatosensory interventions on somatosensory impairment, motor impairment, functional activity and participation after stroke. METHODS: Biomedical databases Ovid Medline, EMBASE, Web of Science, PEDro, and OTseeker were searched with an update in May 2018. Randomized controlled trials investigating the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 43 publications
0
26
0
5
Order By: Relevance
“…They found moderate evidence that somatosensory stimulation does not improve motor performance. Yilmazer et al (13) on the other hand, showed limited evidence for passive somatosensory therapy and some evidence for the effect of active somatosensory therapy on motor function. Nevertheless, when aiming at improving motor function, a pure somatosensory approach may not be sufficient as it is known that task-specific motor training is effective in improving motor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…They found moderate evidence that somatosensory stimulation does not improve motor performance. Yilmazer et al (13) on the other hand, showed limited evidence for passive somatosensory therapy and some evidence for the effect of active somatosensory therapy on motor function. Nevertheless, when aiming at improving motor function, a pure somatosensory approach may not be sufficient as it is known that task-specific motor training is effective in improving motor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the use of a constant sensory stimulation (mechanical vibration on the wrist) during motor rehabilitation has proven efficient in enhancing the motor function both at short and long terms and in increasing motor related brain activity ( Fleming et al, 2015 ). Also, exteroceptive and proprioceptive stimulations seem to have a beneficial influence on motor function, even though further high quality studies are required ( Yilmazer et al, 2019 ).…”
Section: The Interconnection Of Somatosensory and Motor Abilities Durmentioning
confidence: 99%
“…Ebenfalls verbesserte sich ihre Zwei-Punkt-Diskriminierung: Die Schwellenwerte waren am Ende des Trainings signifikant besser als zu Beginn [11]. Diskriminationstraining wird häufig bei chronischen Schmerzen eingesetzt [12], und es gibt mehr Studien zum Diskriminationstraining bei Schmerzen als zur Verbesserung von Körperfunktion [3].…”
Section: Grundsatz Des Diskriminations Tr Ainingsunclassified
“…Eine aktuelle Übersichtsarbeit aus dem letzten Jahr beschrieb den aktuellen Stand zum sensorischen Beüben der oberen Extremität [3]. Die Arbeitsgruppe um Yilmazer und Verheyden aus Leuven, Belgien, zeigte, dass die Effekte somatosensorischer Interventionen auf die Motorik und Funktion der oberen Extremität nach Schlaganfall lediglich gering sind.…”
unclassified
See 1 more Smart Citation